PERSEPSI MASYARAKAT TENTANG PENGGUNAAN APLIKASI MEDIA SOSIAL PADA ANAK REMAJA DI DESA PASAR UJUNG BATU KECAMATAN SOSA KABUPATEN PADANG LAWAS - Siska Siregar, Dewi; Rozi, Fakhrur; Fernanda Desky, Ahmed (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
This study aims to find out how people perceive the use of social media applications in adolescents in Pasar Ujung Batu Village, Sosa District, Padang Lawas Regency. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. The results of the study show that the various perceptions of parents of teenagers in Pasar Ujung Batu Village range from positive, negative and neutral. There are positive and negative impacts on adolescent users of social media, while the positive impacts obtained by adolescents using social media are: strengthening friendships, increasing friends, being easy to get along with, increasing knowledge, a place for discussion, a place to pour out one's heart, a place for storing personal data. While the negative impacts on young social media users are: Imitation behavior, offense, reduced relationship with the surrounding environment, lack of attention to family, forgetting time, and reduced study time. Teenagers of Pasar Ujung Batu Village, Sosa District, Padang Lawas Regency use social media not only to seek entertainment by watching videos and chats that are presented there, but also to act as content creators. However, there are impacts that many parents complain about, such as their children tend to often make dance content that is considered bad and even neglect what is required of them.